Drug utilization pattern in outdoor patients of pediatric tertiary care hospital: a cross sectional study - Parekar, Sonal M.; Maindarkar, Girish K.; Maindarkar, Vishal V. (International Journal of Basic & Clinical Pharmacology, 2020)
Background: Drug utilization study is essential, as safe and effective therapeutic regimen in paediatric population is challenging. Pattern of use of drugs in pediatrics vary as compared to adults, also there is limited data available. The objective of this study was to study drug utilization pattern in pediatric patients attending pediatric outpatient department of Maindarkar pediatric hospital, Latur. Methods: A cross sectional study was carried out for a period of six months from September 2019 to February 2020, by analysing a total 1000 prescriptions of patients who had visited the OPD of Maindarkar pediatric hospital. Prescriptions were selected by simple random sampling method. Results: In our study, out of the total of 1000 prescriptions, 244 (24.4%) were of neonates, 556 (55.6%) were of infants (1 month to 1 year) and 200 (20%) were of children above 1 year. 547 (54.7%) prescriptions were of male patients and 453 (45.3%) were of female patients. The most frequent classes of drugs prescribed were nonsteroidal anti-inflammatory drugs 704 (70.4%), followed by drugs used for respiratory disorders 655 (65.5%) and supplements (60%). Antimicrobials were prescribed in 498 (49.8%) prescriptions. The average number of drugs per prescription was 2.45. About two third of all the prescribed drugs (74.41%) were from national essential medicine list. Most of the prescriptions had oral drug formulation 825 (82.5%) followed by inhalational 208 (20.8%) followed by injectables 150 (15%). All the drugs were prescribed by brand names. Conclusions: Our study helps health-care system to understand, interpret and improve prescribing, administration, to minimize adverse events and promote rational use of medicines.